Diabetes Mellitus Is Associated With an Exocrine Pancreatopathy: Conclusions From a Review of Literature. Issue 8 (September 2016) - Mohapatra, Sonmoon; Majumder, Shounak; Smyrk, Thomas C.; Zhang, Lizhi; Matveyenko, Aleksey; Kudva, Yogish C.; Chari, Suresh T.
Abstract : Objective: Abnormalities in exocrine pancreatic function have been reported in diabetes mellitus (DM). We reviewed published literature to determine the nature of structural and functional alterations in the exocrine pancreas in DM. Methods: We identified and abstracted data from original studies (n = 50) describing morphological, structural, and functional changes in the exocrine pancreas in types 1 and 2 DM. Results: Pancreatic weight and volume are markedly lower in type 1 DM ( P < 0.005) with insignificant decrease in type 2 DM compared with age-, sex-, and body mass index–matched controls. Pancreatic histopathological changes seen in most subjects with DM at autopsy (n = 7 studies, 1272 autopsies) include mild-to-marked interacinar fibrosis, scant inflammatory infiltrate, no pancreatic ductal changes, and hyalinization of arteries. In subjects with DM, pooled prevalence of decreased fecal elastase 1 (<200 μg/g) is higher, coefficient of fat absorption is near normal (mean, 91%–94%), and pancreatic exocrine dysfunction is nonprogressive over time. Diabetes mellitus is asymptomatic in regard to the exocrine pancreas. Conclusions: In types 1 and 2 DM, moderate-to-severe subclinical pancreatic fibrosis and modest exocrine dysfunction occurs in the absence of clinical or histopathological evidence of chronic pancreatitis. We call this novel entity "diabetic exocrine pancreatopathy." Abstract : Supplemental digital content is available in the text.